(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Psychiatric disorders are more prevalent among women than men worldwide. The lifetime risk of depression and dysthymia are twice as common in women as men. Rural women usually undergoes more stressful situations and also scores more on stress scale than that of urban and slum population. Objectives: The research objectives of this study are: 1) To find out the prevalence of psychiatric disorders among the study population. 2) To compare the disorders among the rural and slum female population. 3) To find out the influence of existing socio-demographic factors on psychiatric disorders. Method: This is a community-based study, which is also cross sectional and descriptive in nature. The sample for the main study constituted 366 randomly selected respondents. A two-staged screening procedure was carried in the study. First, the total population was studied by screening test-Self Reporting Questionnaire (SRQ) to divide the sample into ’screen positive’ and ’screen negative’ subjects. In the second stage, full assessment of a mixture of all ’screen positive’ and 25% ’screen negative’ was carried out by structured clinical interview for diagnosis (SCID-NP). Later SCID filled by the respondents was assessed by consultant psychiatrists by using DSMIV in order to put exact clinical diagnosis. Stress was scored according to Presumptive Stressful Life Events Scale (PSLE). The total duration of the study was from July 2010 to June 2011. Results: Higher prevalence of psychiatric morbidity was found among rural sample (22.8%) than slum (10.90%) population. Regarding pattern of psychiatric disorders among rural sample (22.8%) than slum (10.9%) population. See the PDF for the rest of the abstract.